2006
DOI: 10.1016/j.neuroimage.2006.04.185
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of interictal FDG-PET metabolism and ictal SPECT perfusion changes in human temporal lobe epilepsy with hippocampal sclerosis

Abstract: Interictal hypometabolism in mTLE-HS was greatest in the ipsilateral frontal lobe and represented a seizure-related dynamic process in view of further ictal decreases. Crossed cerebellar diaschisis suggested that there is a strong ipsilateral frontal lobe inhibition during CPS. We speculate that surround inhibition in the frontal lobe is a dynamic defense mechanism against seizure propagation, and may be responsible for functional deficits observed in mTLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 48 publications
8
93
2
1
Order By: Relevance
“…The spatial pattern of this network was similar to that of the temporal epileptic network reported in other studies using different imaging modalities [Bernhardt et al, 2008;Blumenfeld et al, 2004;Spencer, 2002;Tae et al, 2005]. Although a general consensus has been reached that the hippocampus is the key of the epileptogenic focus, increasing evidence has shown that widespread brain structures, including the bilateral mesial temporal structures [Bernhardt et al, 2008;Seidenberg et al, 2005;Spencer, 2002], neocortices such as the lateral temporal [Blumenfeld et al, 2004;Tae et al, 2005] and parietal lobes [Englot et al, 2008;Nelissen et al, 2006;Tae et al, 2005], subcortical structures such as the thalamus [Labate et al, 2008;Schwarcz et al, 2002;Yune et al, 1998], basal ganglia and pontine nuclei [Bouilleret et al, 2005] etc., compose a reciprocal mesial temporal epileptic network contributing to the process of mTLE [Blumenfeld et al, 2004;Sakamoto et al, 2003;Spencer, 2002]. The largely overlapped results might implicate that the widespread increased ALFF is underpinned by the mesial temporal epileptic network proposed by Spencer [2002].…”
Section: Regions Showing Increased Alff and The Temporal Epileptic Nesupporting
confidence: 82%
“…The spatial pattern of this network was similar to that of the temporal epileptic network reported in other studies using different imaging modalities [Bernhardt et al, 2008;Blumenfeld et al, 2004;Spencer, 2002;Tae et al, 2005]. Although a general consensus has been reached that the hippocampus is the key of the epileptogenic focus, increasing evidence has shown that widespread brain structures, including the bilateral mesial temporal structures [Bernhardt et al, 2008;Seidenberg et al, 2005;Spencer, 2002], neocortices such as the lateral temporal [Blumenfeld et al, 2004;Tae et al, 2005] and parietal lobes [Englot et al, 2008;Nelissen et al, 2006;Tae et al, 2005], subcortical structures such as the thalamus [Labate et al, 2008;Schwarcz et al, 2002;Yune et al, 1998], basal ganglia and pontine nuclei [Bouilleret et al, 2005] etc., compose a reciprocal mesial temporal epileptic network contributing to the process of mTLE [Blumenfeld et al, 2004;Sakamoto et al, 2003;Spencer, 2002]. The largely overlapped results might implicate that the widespread increased ALFF is underpinned by the mesial temporal epileptic network proposed by Spencer [2002].…”
Section: Regions Showing Increased Alff and The Temporal Epileptic Nesupporting
confidence: 82%
“…F-FDG PET and a high-resolution 3D T1-weighted Magnetization Prepared Rapid Acquisition Gradient Echo (3D-MPRAGE) MR scan of twenty neurologically normal volunteers (9 male/11 female, median age: 29 (range 21-49)) were available from a previous study approved by the Local Ethics Committee (30). Informed consent had been obtained from all participants before the investigations.…”
Section: Healthy Volunteersmentioning
confidence: 99%
“…The reconstructed images of the patient data were first flipped if needed to make sure the epileptogenic focus was always at the left side. All reconstructions of the measured human data were then first normalized to cancel out differences in average WM activity, as proposed in (30). Next, these images were spatially normalized to the stereotactic Montreal Neurological Institute (MNI) space using the non-linear warping obtained during MR segmentation.…”
Section: Spm Analysismentioning
confidence: 99%
“…8,9 If scalp interictal and ictal EEG do not adequately localise the area of seizure onset, it may be necessary to undertake intracranial EEG recordings, with intracerebral depth electrodes and/or subdural strips and grids of electrodes (Fig 3). These are a major undertaking with a risk of significant morbidity.…”
Section: The Evaluationmentioning
confidence: 99%